Análisis y actualización de los trámites municipales del Departamento de Ordenamiento Territorial de la Municipalidad de Alvarado - Martínez-Martínez, Mario Alberto (Instituto Tecnológico de Costa Rica, 2016)
This report shows the results obtained from the updating of municipal procedures of Land Management Department, belonging to Municipality in Alvarado. A diagnosis of the Department’s present situation was realized, finding it was necessary to improve the documents and procedures to solve the formalities; therefore, the respective documentation was elaborated. A “Technical Procedures Manual to Solve Municipal Formalities” was made, in order to collaborate with civil servants in execution of formalities, as well as a “Guide of Requirements for Municipal Formalities”, directed to municipality’s user, so they knew necessary information to request a management. In addition, there was a collaboration with the Department of Municipal Services Platform through trainings, so they reinforce their knowledge in formalities resolution matters. It was founded that Local Government in Alvarado lacks of civil servants, produced by the great amount of everyday tasks; a failure to update and have statutes, and the implementation of Platform Department without any previous workers training, documentation or internal regulation. In conclusion, the results included in this project will help to improve internal management of Municipality in Alvarado, giving it competitiveness against other Local Governments of the country.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Documentación; Ayuntamientos; Soluciones; Procedimientos; Trámites del Sector Público; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture